A highly resistant structure between cuticle and cortex of human hair. (4th December 2016) - Takahashi, T.; Yoshida, S.
Abstract: Objective: To clarify the presence and properties of a unique structure which is located between the cuticle and cortex of human hair. Methods: Whole hair fibre and longitudinally split hair were used. Treated with a mixture of urea, reductant and alkaline, hair was split at the interface between cuticle and cortex. The residues in the solution were observed by microscope, and the distribution of lipids and protein was determined. Results: From the treated longitudinally split hair, a membrane‐like structure which was located at the interface between cuticle and cortex was obtained. This structure showed especially high resistance against chemical treatment and was thought to be the region into which the proximal roots of the cuticle cells are embedded. It was supposed that some steryl glucoside‐like lipid, of which the presence in the cuticle and cortex interface was previously reported, is located in this structure. Conclusion: This study proposed the presence of a membrane‐like structure, which is highly resistant against chemical treatment, at the region between cuticle and cortex of human hair. This may protect cortex from external stimuli more firmly than the surface part of cuticle.